(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Climate change is the long-term alteration of temperature and typical weather patterns in a place where it usually causes weather patterns to be less predictable. These unexpected weather patterns can make it difficult to maintain and grow crops in regions such as the developing countries like India where around 60 per cent of the population rely on monsoon for their agriculture because expected temperature and rainfall levels can no longer be relied on.